Didactic Unit for teaching Analytical Geometry in tenth grade of the Costa Rican Diversified Education, applying problem-solving and technology - Araya Benavides, Wendy (2023)
The aim of this article is to describe the results obtained in the work entitled "Teaching Unit for the Approach of Analytical Geometry in Tenth Year of Diversified Education, Applying Problem Solving and Technology", exposing the feasibility of a teaching unit directed to the teacher, in which the GeoGebra software is used as a support tool to present the contents of analytical geometry using problem solving. It is concluded that the use of the software favors the understanding of the contents, since the students can manipulate the geometric figures and, at the same time, see the change in their algebraic representation, with which the learner is able to generate their own knowledge.